ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2009-2011) - Estrini, Dwi Hayu; Laksito, Herry (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to examine the impact of profitability, company size, auditors gender, and reputation of accountant firms influence simultaneously toward audit delay in manufacturing company that listed on the Indonesia Stock Exchange from 2009 to 2011.Data that used in this research is financial statements from each company, publized through website www.idx.co.id. This study used purposive sampling methods. The data which have already collected are processed with classic assumption test before hypothesis test. The results of this study show that of profitability, auditors gender and reputation of accountant firms significant effect toward audit delay, Whereas, company size do not influence time of audit delay.Â